CYTOLOGICAL ASSESSMENT OF DOUBLED HAPLOIDS IN SUMMER SQUASH (CUCURBITA PEPO L.) - E. A. Domblides; L. Yu. Kan; G. A. Khimich; I. B. Korotseva; A. S. Domblides (Овощи России)
147 new forms were obtained only from nine responsive unpollinated ovules of summer squash in 2015-2017. The cytological analysis is used to estimate the level of ploidy in regenerated plants R0. The small size of mitotic chromosomes and large number in Cucurbita genus make it difficult to count them even though they are well separated. As a result of analysis the optimal method of chromosome staining has been chosen with the use of modified propiono- lacmoid cytological technique. The rootlet tips and apical meristems were used to make smear preparations. As it was shown the summer squash was a difficult species as a cytological object because of low mitosis frequency and low number of metaphase plates with well scattered chromosomes. The photos of chromosomes in squash C. pepo subsp. brevicaulis var. giraumons Duch; distant hybrid (breeding accession N37) between variety ‘Cornishon’ and winter squash C. pepo subsp. longicaulis Greb. var. pepo and doubled haploid plants produced from them were made. In spite of the small size 2 μm the chromosomes observed were clearly seen. Nearly all regenerated plants that had been analyzed passed well the adaptation in vivo and occurred to be a doubled haploids (2n = 2x=40). The seed progeny was then obtained through self-pollination. About 20% of plants R0 analyzed were mixploids and supposedly only 7% were haploids.